Opportunities for implementing improved tree seed sourcing for forest landscape restoration, agroforestry and wider tree planting at the project design stage: Findings of a survey of planters, researchers and funders - Carsan, S.; Dawson, Ian K.; Kindt, R.; Lillesø, Jens-Peter B.; Pedercini, F.; Chege, J.; Jamnadass, Ramni; Graudal, L. (World Agroforestry Centre, 2021)
Current tree-planting initiatives are not always successful in achieving their stated targets of biodiversity conservation, climate change mitigation and human livelihood improvement. This is in part due to a lack of attention to the proper sourcing of the tree seeds and seedlings that are used. In this working paper, we explore these sourcing issues by reporting on an online survey undertaken in 2021 with tree planters, researchers and funders. The aim of this working paper is to assess the feasibility of redesigning the design templates of planting project proposals to include tree seed sourcing information, with the outcome of increasing support for improved sourcing practices. The survey results for 173 respondents (comprising 90 planters, 69 researchers and 14 funders collectively working globally, embracing the Global South and Global North) suggested that there is scope at the project design stage to require (potential) tree planters – who are applying for financial support to carry out tree planting – to explain how they will source tree seed. The majority of funders were willing to adopt such an approach, and most survey participants overall considered that it is important for tree planters to explain how they will undertake tree-seed sourcing.